2013
DOI: 10.1098/rspb.2013.1553
|View full text |Cite
|
Sign up to set email alerts
|

Escalation of aggressive vocal signals: a sequential playback study

Abstract: Rival conspecifics often produce stereotyped sequences of signals as agonistic interactions escalate. Successive signals in sequence are thought to convey increasingly pronounced levels of aggressive motivation. Here, we propose and test a model of aggressive escalation in black-throated blue warblers, presenting subjects with two sequential and increasingly elevated levels of threat. From a speaker outside the territorial boundary, we initiated an interaction (low-threat level), and from a second speaker insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…Game theoretical models of aggressive behaviour (reviewed in [1][2][3]) and empirical tests in both vertebrates [4,5] and invertebrates [6,7] find that competitors use signals to resolve contests before escalating to dangerous combat. Some mantis shrimp species (Stomatopoda) use their raptorial appendages to crack and kill hard-shelled prey with strikes that deliver forces exceeding their body weight by a thousand times or more [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Game theoretical models of aggressive behaviour (reviewed in [1][2][3]) and empirical tests in both vertebrates [4,5] and invertebrates [6,7] find that competitors use signals to resolve contests before escalating to dangerous combat. Some mantis shrimp species (Stomatopoda) use their raptorial appendages to crack and kill hard-shelled prey with strikes that deliver forces exceeding their body weight by a thousand times or more [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that some behaviors that were previously thought to reflect attack intent are not actually correlated with attack (Ballentine et al 2008;Hof and Hazlett 2010;. Thus, it is insufficient to assume that the closeness of the receiver is a cost of to the soft song signaler (Hof and Hazlett 2010;Hof and Podos 2013). The present study showed that when soft song was played back, more subject males conducted attacks of the mounted specimen with shorter attack latencies.…”
Section: The Cost Of Soft Songmentioning
confidence: 60%
“…Ballentine et al 2004) and male-male territorial conflicts (Illes et al 2006) to assess the quality of singing individuals. In our study system, males approached song stimuli ending with broad frequency bandwidths and fast syllable repetition more closely, possibly because males singing at the performance limits represent a greater threat in terms of likelihood of cuckoldry or territorial takeover (Hof and Podos 2013). Lowland males do not sing faster trills but do produce songs ending in broader bandwidths, and qualitatively tend to display a superior song performance with respect to highland males (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…In parallel, the value of male parental effort should increase, triggered by the low likelihood of cuckoldry and by substantial gains in offspring survival due to male care in the restrictive environmental conditions (Moller and Birkhead 1994;Badyaev and Ghalambor 2001;Hille and Cooper 2015). Since the attack of song stimuli is considered an unambiguous assay of aggression (Hof and Podos 2013), the longer distances of approach displayed by high elevation water pipits may be interpreted as the result of reduced aggressive motivation and, more broadly, weaker strength of intrasexual selection (i.e., fewer fitness benefits of male-male competition). A similar pattern has been observed in the black redstart Phoenicurus ochruros, in which highland males had weaker responses to intruder stimuli than lowland ones (Apfelbeck and Goymann 2011).…”
Section: Discussionmentioning
confidence: 99%